Diseño del departamento de relaciones públicas en la cooperativa de taxis capitán Luis Nieto Pico de Guayaquil - Mera Sobrevilla, Kelly Katherine (2014)
This work is the result of the strategic action of communication of the cooperative of taxi “Capitan Luis Nieto Pico”, whereas the term information society, vital in their development as business underway to maintain its brand positioned and the correct identification of its customers. He is emphasized as a priority for the implementation of the Department of public relations, having the personnel for the management of institutional information, have the technological tools for communication with official or customers and the creation of a data base that allows contacting customers to obtain benefits for donors and in turn to the cooperative......